Excessive Targeting - Heiko Karle (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We consider a market with two symmetric firms and two asymmetric consumer groups. Firms send advertising messages which inform consumers about the existence and the price of their product (Butters, 1977). Targeting a specific consumer is imperfect as with some probability the consumer is not reached. We show that a higher targeting probability has a non-monotone effect on firms' profit. If the probability of successfully targeting a specific consumer is low, all firms target the high-type consumer and more fine-tuned targeting amplifies price competition between firms and decreases firms' profit (competition for cherries). If the probability of successfully targeting is sufficiently high, however, more fine-tuned targeting increases firms' profit because firms segment the market by targeting different consumers. This reduces the competitive pressure for firms. We also characterize conditions under which firms prefer no targeting to perfect targeting technologies.
Keywords: D43; M37; 330; Targeted advertising; Informative advertising; price competition